2016
DOI: 10.1002/jcop.21823
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Substance Use Among Native American Early Adolescents

Abstract: The overall objective of this study was to examine the effects of an innovative culturally appropriate school‐based intervention. Cherokee Talking Circle (CTC), for the prevention of substance use among 100 Keetoowah‐Cherokee 6th graders as they transition to middle school. The impact of the CTC on substance use involvement (measured by the Global Assessment of Individual Needs – Quick) and Cherokee self‐reliance (measured by the Cherokee Self‐Reliance Questionnaire) was assessed using a two‐condition quasi‐ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Across studies, the most commonly utilized cultural-based measures sought to assess AI/AN/NH cultural identity, social connectedness, and spirituality. Additional cultural-based scales utilized among IRINAH-funded studies included: Native Reliance (Lowe, Liang, & Henson, 2016; Lowe, Riggs, Henson, & Liehr, 2009), Health Impact Assessment Tool (HIA) (which utilized an iterative process based on discussions in English and the Choctaw language) (HIP, n.d.), a 5-item version of the Oppression Questionnaire (Victoroff, 2005), Awareness of Connectedness Scale (Mohatt, Fok, Burket, Henry, & Allen, 2011), and Historical Losses Scale (Whitbeck, Adams, Hoyt, & Chen, 2004). Measures of several other critical constructs included: the Alaska Native Wellness measure (Wolsko, Lardon, Hopkins, & Ruppert, 2006), traditional use of tobacco, boarding school attendance, perceptions of the boarding school experience, engagement in traditional Native activities, social connectedness using the Interpersonal Needs Questionnaire (Van Orden, Cukrowicz, Witte, & Joiner, 2012; Van Orden, Witte, Gordon, Bender, & Joiner, 2008), and Reflective Processes (adapted from the adult Yup’ik Protective Factors scale; Allen et al 2012).…”
Section: Gathering the Medicine (Results)mentioning
confidence: 99%
“…Across studies, the most commonly utilized cultural-based measures sought to assess AI/AN/NH cultural identity, social connectedness, and spirituality. Additional cultural-based scales utilized among IRINAH-funded studies included: Native Reliance (Lowe, Liang, & Henson, 2016; Lowe, Riggs, Henson, & Liehr, 2009), Health Impact Assessment Tool (HIA) (which utilized an iterative process based on discussions in English and the Choctaw language) (HIP, n.d.), a 5-item version of the Oppression Questionnaire (Victoroff, 2005), Awareness of Connectedness Scale (Mohatt, Fok, Burket, Henry, & Allen, 2011), and Historical Losses Scale (Whitbeck, Adams, Hoyt, & Chen, 2004). Measures of several other critical constructs included: the Alaska Native Wellness measure (Wolsko, Lardon, Hopkins, & Ruppert, 2006), traditional use of tobacco, boarding school attendance, perceptions of the boarding school experience, engagement in traditional Native activities, social connectedness using the Interpersonal Needs Questionnaire (Van Orden, Cukrowicz, Witte, & Joiner, 2012; Van Orden, Witte, Gordon, Bender, & Joiner, 2008), and Reflective Processes (adapted from the adult Yup’ik Protective Factors scale; Allen et al 2012).…”
Section: Gathering the Medicine (Results)mentioning
confidence: 99%
“…Studies also set out to understand the link between historical trauma and chronic physical illnesses (11 studies). Of the 13 interventional studies with North American Indigenous groups, studies included improving coping strategies and decreasing anxiety, depression, and PTSD (Goodkind et al, 2010), preventing substance abuse (Lowe et al, 2016), and managing obesity (Kelley & Lowe, 2018). Most studies pursued purposes that targeted outcomes in specific subpopulations, including Indigenous women (Dodgson & Struthers, 2005), homeless Indigenous adults (Bingham et al, 2019), and persons who had been compelled to undergo residential schooling (Howard, 2014).…”
Section: Purposementioning
confidence: 99%
“…Among these were two studies that trialed educational interventions to reduce physical chronic illnesses, three studies that described and/or evaluated interventions to strengthen ethnic identity and empower Indigenous persons, two studies that described programs to provide Indigenousspecific care, and six studies that described and/or evaluated programs to decrease specific behaviors described as maladaptive (Table 2). Interventions included a study with American Indian youth conducted by Lowe et al (2016) that compared effects on substance use and general well-being following a Cherokee Talking Circle (CTC) intervention compared with a nonculture-based intervention. Barnett et al's (2020) assessment of a culture camp for Alaska Native youth at risk for suicide found that cultural activities with an emphasis on relationship building, role modeling, and sharing struggles significantly increased positive mood, feelings of belongingness, and self-perceived coping and decreased the risk of suicide.…”
Section: Addressing Historical Trauma Through Interventions and Programsmentioning
confidence: 99%
“…Stratification of participant responses by age and gender is not typically done when using the CQR analytical method. The stories and themes were correlated with the Native‐Reliance theoretical framework and model core concepts (Hill et al, ; Lowe et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Native‐Reliance theoretical framework and model guided the interpretation of the findings of the study (Lowe, Liang, Henson, & Riggs, ). The Native‐Reliance theoretical framework, model, and questionnaire emerged in response to the limited available Native American theoretical frameworks.…”
Section: Theoretical Conceptual Frameworkmentioning
confidence: 97%